Identifikasi Organisasi dan Program Ruang Creative Hub - Khoirunnisa, Khoirunnisa; Pramantha, Raudina Qisthi (Universitas Syiah Kuala, 2024)
This study examines the spatial organization and programming of two creative hubs in Indonesia: Jakarta Creative Hub and Bandung Creative Hub). The research aims to analyze how spatial design supports creative activities and fosters collaboration among creative practitioners. Both hubs employ a grid-based spatial organization, categorizing spaces by specific functions such as coworking, workshops, and public zones. While Jakarta Creative Hub emphasizes zones for collaboration, production, and training, Bandung Creative Hub integrates spaces for art exhibitions, multimedia production, and educational activities. This study highlights the importance of balancing specific and flexible spaces, with specialized areas like the Fashion Lab and Woodworking Area facilitating targeted activities, and coworking spaces and exhibition areas providing adaptability for various events. The findings demonstrate that the grid-based spatial design of both hubs enhances efficiency and allows structured arrangements to meet diverse needs, ultimately fostering creativity and collaboration within the creative ecosystem. Keywords: Cretive Hub, Organisasi Ruang, Program Ruang.